2012
DOI: 10.2190/om.65.2.a
|View full text |Cite
|
Sign up to set email alerts
|

Participants with Prolonged Grief—How Do They Benefit from Grief Group Participation?

Abstract: Data analyzed in this article is part of a study conducted to explore grief support groups in Norway. Participants that fulfilled the criteria of Prolonged Grief Disorder (PGD) were compared with participants that did not in order to explore whether they differed on satisfaction and experiences with participation. To allow for comparison, a subsample of 22 participants that fulfilled the criteria of PGD were drawn from the total of 262 participants. Demographic and loss-related variables were analyzed to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…The results of the present study indicate that female parents, the subjective nonwealthy family economic status, older age of the parents at the time of child loss, and a short duration since child loss are associated with higher symptomatic severity of PGD. This study's regression analysis indicated that fewer years since loss, subjective perception of poor economic situation, and female gender were prominent risk factors for the development of PGD, which is compatible with the findings of many prior studies on the duration since child loss (Coelho et al, 2015;Heeke et al, 2015;Keesee et al, 2008;McCarthy et al, 2010;Schaal et al, 2010), family's economic status (McCarthy et al, 2010;Yi et al, 2018), and female gender (Johnsen et al, 2012;Lai et al, 2015;Morina et al, 2010;Neria et al, 2007;Schaal et al, 2014;Xiu et al, 2016). These risk factors are particularly valuable in screening for PGD in Shidu parents in the future.…”
Section: Strengths and Clinical Implicationssupporting
confidence: 88%
See 1 more Smart Citation
“…The results of the present study indicate that female parents, the subjective nonwealthy family economic status, older age of the parents at the time of child loss, and a short duration since child loss are associated with higher symptomatic severity of PGD. This study's regression analysis indicated that fewer years since loss, subjective perception of poor economic situation, and female gender were prominent risk factors for the development of PGD, which is compatible with the findings of many prior studies on the duration since child loss (Coelho et al, 2015;Heeke et al, 2015;Keesee et al, 2008;McCarthy et al, 2010;Schaal et al, 2010), family's economic status (McCarthy et al, 2010;Yi et al, 2018), and female gender (Johnsen et al, 2012;Lai et al, 2015;Morina et al, 2010;Neria et al, 2007;Schaal et al, 2014;Xiu et al, 2016). These risk factors are particularly valuable in screening for PGD in Shidu parents in the future.…”
Section: Strengths and Clinical Implicationssupporting
confidence: 88%
“…Several studies have reported risk factors associated with the development of prolonged grief in different population samples, including gender, age (Chiambretto, Moroni, Guarnerio, Bertolotti, & Prigerson, 2010), time since loss (Chiambretto et al, 2010;Coelho, Delalibera, Barbosa, & Lawlor, 2015;Heeke, Stammel, & Knaevelsrud, 2015;Keesee et al, 2008;McCarthy et al, 2010;Schaal, Jacob, Dusingizemungu, & Elbert, 2010), cause of loss (Boelen, 2015;Keesee et al, 2008;McCarthy et al, 2010), family's economic status (McCarthy et al, 2010;Yi et al, 2018), religious beliefs (Schaal et al, 2014), emotional closeness to the deceased (Schaal et al, 2014); but produced inconsistent conclusions. For instance, some studies (Neria et al, 2007;Morina, Rudari, Bleichhardt, & Prigerson, 2010;Johnsen, Dyregrov, & Dyregrov, 2012;Schaal et al, 2014;Lai et al, 2015;Xiu et al, 2016;Yi et al, 2018, Yin, Shang, et al, 2018Yin, Sun, et al, 2018) found that the female gender was a predictor for prolonged grief, and one study (Li, Laursen, Precht, Olsen, & Mortensen, 2005) reported that bereaved mothers had a relatively high risk of being hospitalized for any psychiatric disorder as compared with bereaved fathers, while other authors reported no significant association between grief and gender (Boelen & van den Bout, 2005;Momartin, Silove, Manicavasagar, & Steel, 2004;Schaal et al, 2010). There is limited research about potential risks of PGD in the Chinese population (He et al, 2014), much less in Shidu parents.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it changes the way distressing thoughts are processed rather than addressing the content. This bodes well for treating grief in a group setting, as individuals with PGD have been found to be less satisfied with group participation due to co-rumination (conversations with others about the loss) 38. The intervention comprised six, 2-hour sessions, 1 day per week.…”
Section: Methodsmentioning
confidence: 99%
“…As was reflected both in the interviews as well as in the PG-13 measures in the quantitative part, participants who were less satisfied with grief group participation than the rest of the participants also had the highest level of PGD (Johnsen et al, 2012). Lack of realistic expectations resulted in some of them turning down offers of trauma-specific help and entering grief groups instead.…”
Section: Screening Is Needed For Traumatized Bereavedmentioning
confidence: 96%